Jalaukavacharana (Leech Therapy) – A Review Article - Sindhi, Sana Kausar; Meena, Namo Narayan; Soni, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2025)
In the Sushruta Samhita, Jalaukavacharana (leech therapy) is first described. Numerous inflammatory, ischemic, and viral disorders may be effectively treated using leech therapy, also known as Jalaukavacharana, an age-old Ayurvedic bloodletting method. Raktamokshana by means of “leech” falls under the Ashastra category and is thought to be the most effective and distinctive way because it removes vitiated Doshas from the body without the need for any cutting tools. Jalaukavacharana refers to the use of leeches in treatment.